Evaluation of implementation of food safety legislation in the red meat abattoirs of Mopani District, Limpopo Province, South Africa - Gana, Shalati (University of Limpopo, 2014)
Introduction: To evaluate the food safety legislation (FSL) implementation in the red meat abattoirs of Mopani district in Limpopo Province, South Africa. Method: A cross sectional survey was conducted. Sampling: A questionnaire was distributed to abattoir managers of various red meat abattoirs. From 16 abattoirs with a population 169, a sample of 22 was selected. Results: The study revealed that 77% managers were male. Majority of managers were aged 40 and 59 years. Work experience was between 20 to 25 years. Educational background: thirty seven percent (37%) of managers hold certificates on various disciplines, mostly not food safety related. Fifty-four percent (54%) managers did not have food safety knowledge. Fifty-nine percent (59%) abattoirs did not comply with food safety practices. Twenty seven percent (27%) of the structures did not comply with R.1072. The pieces of FSL were less implemented by DoH&SD and DTI. Hygiene Management Systems showed slow progress. Sixty-four percent (64%) abattoirs did not receive training on HMS and PRPs. Very few abattoirs had multi-disciplinary skilled personnel to implement FSL. Abattoirs were reluctant to financial commitment to implement FSL. Eighty two percent (82%) of abattoirs did not involve all stakeholder during planning and decision making process. Conclusion: The red meat abattoirs of Mopani district did not comply with all standards and requirements of food safety legislation. Factors such as educational background in basics of food safety principles, involvement of role players during implementation process, prevented successful implementation of food safety legislation in the red meat abattoirs of Mopani district. Food safety knowledge and practices of management and malpractice of FSL were determined, results showed that majority lack adequate food safety knowledge and poor food safety practices were identified. One of the recommendation was to establish FSL enforcement forum to develop a FSL strategy.
Thesis ( MPH.) --University of Limpopo,2014.
Keywords: Food safety legislation; Red meat abattoirs; Food -- Law and legislation; Beef -- South Africa